Genome‐wide identification of catfish antimicrobial peptides: A new perspective to enhance fish disease resistance. (2nd May 2022) - Wang, Jinhai; Su, Baofeng; Dunham, Rex A.
Abstract: Antimicrobial peptides (AMPs), also known as host defence peptides, are evolutionarily ancient defensive weapons that can combat infections caused by pathogens. Fish‐derived AMPs have shown microbicidal properties, host immunomodulatory responses, and are induced by a variety of factors, especially pathogenic infection and abiotic stress, which may activate downstream signalling pathways to initiate the expression of antimicrobial peptide genes. Large‐scale genome sequencing has been applied in many aquatic animals, providing databases for the systematic identification of putative AMPs in these species. Recently, the whole genome and the proteome of channel catfish ( Ictalurus punctatus ) were released; by taking advantage of the antimicrobial peptide database and combining the proteome of catfish, we established a bioinformatic analysis pipeline to identify catfish AMP repertoire. This review introduces an effective method for the identification and development of putative AMPs based on protein datasets, and summarizes the structural properties, immunomodulation and molecular responses in vivo of catfish AMPs. In addition, the evaluation of the antibacterial activity of synthetic or isolated AMPs in vitro, and the applications of AMPs in fish via genetic engineering and clustered regularly interspaced short palindromic repeats associated proteins system (CRISPR/Cas9) were presented, which supports antimicrobial research and aquaculture therapy. The summary and comparison of these AMPs will enhance our understanding and their cross‐species applications. Combined with current genetic engineering and genome editing techniques, it is possible to promote the development of immune processes to protect valuable aquatic animals from infectious diseases.